The level of knowledge regarding breast cancer among female high school students at Santo Yoseph School, Denpasar, Bali, Indonesia - Hemalatha Thiruchelvam; Ni Nyoman Ayu Dewi; Ida Ayu Dewi Wiryanthini (Intisari Sains Medis, 2019)
Background: Breast cancer is the second leading cause of death among women around the world. In Indonesia, breast cancer is the leading cause of death among women. Previous studies have shown that female students have limited knowledge of breast cancer. This study is aimed at assessing the level of breast cancer knowledge among female high school students in Santo Yoseph School, Denpasar.Methods: A cross-sectional survey of 96 female high school students in Santo Yoseph School, Denpasar, was conducted using a self-administered questionnaire.Â  Questions asked in the questionnaire were about general knowledge of breast cancer, risk factors towards breast cancer, signs and symptoms of breast cancer and knowledge of Breast Self-Examination. The data was tabulated by scoring only the correct answers and analysed using SPSS version 17 for Windows.Results: The result of the study showed that high school female students had moderate to good knowledge of breast cancer. Fifty-three (55.2%) female students had average knowledge and forty-three (44.8%) female students had good knowledge of breast cancer. The majority of the participants, seventy-five (78.1%) of them, knew that breast cancer was the leading cause of death among women in Indonesia.Conclusion: The recent findings showed that female high school students had good knowledge of breast cancer. Good knowledge of breast cancer is important for girls and women equally.